2021
DOI: 10.3390/foods10081844
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Enterococcus sp. Isolated from Sheep and Goat Cheeses

Abstract: This study aimed to calculate the proportion of antibiotic resistance profiles of Enterococcus faecium, E. faecalis, and E. durans isolated from traditional sheep and goat cheeses obtained from a selected border area of Slovakia with Hungary (region Slanské vrchy). A total of 110 Enterococcus sp. were isolated from cheese samples, of which 52 strains (E. faecium (12), E. faecalis (28), E. durans (12)) were represented. After isolation and identification by polymerase chain reaction and matrix-assisted laser de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
4
16
0
Order By: Relevance
“…Enterococci are a standard element of the non-starter LAB used to produce traditional Mediterranean, Western Balkan countries and Brazilian cheeses from raw milk of sheep, goats and cows [ 1 ]. Enterococci also still play an important role in the production of fermented dairy products, such as some cheeses, in extension of the shelf life and improvement of their taste, texture, and aroma [ 4 ]. According to data provided by various authors, enterococci may occur naturally or as contaminants of milk and dairy products [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enterococci are a standard element of the non-starter LAB used to produce traditional Mediterranean, Western Balkan countries and Brazilian cheeses from raw milk of sheep, goats and cows [ 1 ]. Enterococci also still play an important role in the production of fermented dairy products, such as some cheeses, in extension of the shelf life and improvement of their taste, texture, and aroma [ 4 ]. According to data provided by various authors, enterococci may occur naturally or as contaminants of milk and dairy products [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first or latest cases of antibiotic resistance of chosen foodborne pathogens in different parts of the world. References [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…More recently Výrostková et al . ( 2021 ) reported that isolates of Enterococcus spp. from sheep and goat cheeses showed high antibiotic resistance to vancomycin (84.62%; 44/52 isolates), teicoplanin (84.62%; 44/52 isolates), erythromycin (76.92%; 40/52 isolates), and rifampicin (76.92%; 40/52 isolates).…”
Section: Resultsmentioning
confidence: 99%